Impact of Accounting Practices on The Performance of Micro Enterprises in Ramanathapuram District - H Anis Fathima; C Paramasivan (Journal of Applied Taxation and Policy, 2026)
This study examines the extent of accounting practice adoption and its association with business performance among micro enterprises in Ramanathapuram District, addressing the limited micro-level empirical evidence in rural and semi-urban contexts. A descriptive-analytical quantitative design was employed using primary data collected from 256 micro-enterprise owners through a structured questionnaire. Convenience sampling was adopted due to accessibility constraints. Accounting practice adoption was operationalized using composite indicators (type of system, frequency of record maintenance, and reporting practices), while business performance was measured using self-reported indicators (sales growth, profit consistency, and financial stability). The results indicate that 46.9% of enterprises rely on manual accounting, 35.2% use computerized systems, and 18% use hybrid methods. Chi-square analysis reveals a statistically significant association between accounting practices and business performance (χ² = 18.52, p < 0.05). Further, ANOVA results show significant differences in performance across levels of accounting adoption (F = 6.25, p < 0.05), with higher adoption levels associated with improved performance outcomes. However, the absence of probability sampling and validated measurement scales limits causal inference and generalizability. The study contributes empirical evidence from a micro-enterprise context and highlights the importance of structured accounting adoption, while acknowledging methodological limitations and the need for more rigorous future research.